Characteristic for the local tradition of wood construction in Museum of Building Ethnographic Park in Olsztynek, exposure and use - Chodkowska, Wiesława (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
Construction of the first Heimatmuseum in Königsberg in the years 1909- 1912, which translocated to Olsztynek in the years 1938- 1943. The creators of the museum: the provincial conservator Richard Dethlefsen, university professors Dr. Adalbert Bezzenberger, Dr. Felix Ernst Peiser. The choice of places to search for objects in the field. The most interesting examples of wooden buildings, representative for the then East Prussia regions. Decisions of the founders of the museum preservation: inventory of selected objects, reasons for the decision to build the museum copies of selected objects. Decisions conservation in MBL-PE in Olsztynek after 1945, translocation original building. Examples of folk buildings collected in the museum. Discussion of ways to protect wooden objects in the museum on several levels. One of them is repair performed by its own team consisting of: carpenters, joiners, roofers, blacksmith, locksmith, plumber, electrician, bricklayer and older renovator. Another way to draw attention to the need to protect the wooden buildings is education. Realized through the lessons museum and educational events during which presented different types of buildings, models are shown ways of erecting buildings and decorating architectural details. The museum presents outfits related to wood processing and temporary exhibitions.